2019
DOI: 10.1002/ange.201812862
|View full text |Cite
|
Sign up to set email alerts
|

PhPAd‐DalPhos: Ligand‐Enabled, Nickel‐Catalyzed Cross‐Coupling of (Hetero)aryl Electrophiles with Bulky Primary Alkylamines

Abstract: The base metal‐catalyzed C−N cross‐coupling of bulky α,α,α‐trisubstituted primary alkylamines with (hetero)aryl electrophiles represents a challenging and under‐developed class of transformations that is of significant potential utility, including in the synthesis of lipophilic active pharmaceutical ingredients. Herein, we report that a new, air‐stable Ni(II) pre‐catalyst incorporating the optimized ancillary ligand PhPAd‐DalPhos enables such transformations of (hetero)aryl chloride, bromide, and tosylate elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…With the optimized conditions in hand, the versatility of the semiheterogeneous catalytic system was evaluated (Table 2). The reaction of methyl 4-bromobenzoate with cyclic secondary amines generally gave high yields for the corresponding aryl amines (1,(4)(5)(6)(7). A secondary amine with low steric hindrance also resulted in the desired aryl amine ( 8), but the majority of acyclic secondary amines did not react under these conditions (see Supplementary Information).…”
Section: Resultsmentioning
confidence: 99%
“…With the optimized conditions in hand, the versatility of the semiheterogeneous catalytic system was evaluated (Table 2). The reaction of methyl 4-bromobenzoate with cyclic secondary amines generally gave high yields for the corresponding aryl amines (1,(4)(5)(6)(7). A secondary amine with low steric hindrance also resulted in the desired aryl amine ( 8), but the majority of acyclic secondary amines did not react under these conditions (see Supplementary Information).…”
Section: Resultsmentioning
confidence: 99%
“…[11] In 2016 we disclosed the new ligand PA d-DalPhos (L1,S cheme 1B), featuring trioxaphosphaadamantane (PCg) and di(o-tolyl)phosphino donor fragments spanned by an o-phenylene bridge. [12] Thederived Ni II pre-catalyst (L1)Ni(o-tol)Cl has proven effective in ad iversity of CÀN cross-coupling applications,i ncluding the monoarylation of ammonia, [12] unhindered primary alkylamines, [12] primary amides, [13] and lactams, [13] with aw ide range of (hetero)aryl electrophiles.V ariation of the PR 2 group in PA d-DalPhos has enabled other challenging C À Ncross-couplings,including the N-arylation of cyclopropylamine [14] and hindered primary alkylamines [15] (Scheme 1B). We have also demonstrated that replacing the phenylene backbone of L1 with a3 ,4-thiophenylene linker (ThioPAd-DaPhos) affords Ni catalysts for the C À Nc ross-coupling of unhindered primary alkylamines that operate under mild conditions (25 8 8C, < 1mol %N i),i n amanner that is competitive with BHA.…”
mentioning
confidence: 99%
“…1 Nickel is an attractive alternative to palladium due to its higher abundance, but the air-sensitive Ni(0) complexes, sophisticated ligands, strong reductants, and bases required for C-N bond formations have hampered its use. [2][3][4] Air-stable nickel pre-catalysts have been developed, but require harsh conditions and have a limited substrate scope (Figure 1, a). [5][6][7][8] In combination with electrochemistry, ligated Ni(II) salts catalyze the C-N cross-coupling under mild conditions (Figure 1, b).…”
Section: Mainmentioning
confidence: 99%